2016
DOI: 10.1111/ene.13026
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in early pediatric multiple sclerosis: a case−control study

Abstract: Background Alterations in the gut microbial community composition maybe influential in neurological disease. Microbial community profiles were compared between early onset pediatric multiple sclerosis (MS) and control children similar for age and sex. Methods Children ≤18 years old within two years of MS onset, or controls without autoimmune disorders attending a University of California, San Francisco, USA pediatric clinic were examined for fecal bacterial community composition and predicted function by 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
294
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(319 citation statements)
references
References 34 publications
22
294
3
Order By: Relevance
“…27,38 Interestingly, Jangi et al 7 found increased Methanobrevibacter among 60 RRMS patients compared to controls. Tremlett et al 6 similarly found enrichment of Methanobrevibacter among their patients with pediatric early MS. Castillo Alvarez et al, 8 however, found a lower abundance of Archaea among 30 MS patients compared to controls, suggesting that further investigation of the relationship between Methanobrevibacter and MS is warranted. Importantly, the association between constipation and increased methanogenic archaea is a potential confounder that should be controlled for in future studies, given the high prevalence of constipation in MS. 7,26 Other microorganisms Several other differences in the gut microbiome of MS patients have been identified.…”
Section: Euryarchaeotamentioning
confidence: 93%
See 1 more Smart Citation
“…27,38 Interestingly, Jangi et al 7 found increased Methanobrevibacter among 60 RRMS patients compared to controls. Tremlett et al 6 similarly found enrichment of Methanobrevibacter among their patients with pediatric early MS. Castillo Alvarez et al, 8 however, found a lower abundance of Archaea among 30 MS patients compared to controls, suggesting that further investigation of the relationship between Methanobrevibacter and MS is warranted. Importantly, the association between constipation and increased methanogenic archaea is a potential confounder that should be controlled for in future studies, given the high prevalence of constipation in MS. 7,26 Other microorganisms Several other differences in the gut microbiome of MS patients have been identified.…”
Section: Euryarchaeotamentioning
confidence: 93%
“…Instead, enrichment or depletion of a limited number of taxa seems to be a reproducible finding. 6,7 We systematically review alterations in the gut microbiota that have been identified in patients with MS (see Table 1) and discuss their potential contributions to MS pathogenesis (see Table 2). …”
Section: Introductionmentioning
confidence: 99%
“…Tremlett et al [30] studied the gut microbiota in pediatric patients with relapsing/remitting MS and found that relative to controls, MS cases had a significant enrichment in the relative abundance for members of the Desulfovibrionaceae family and depletion in Lachnospiraceae and Ruminococcaceae (all p < 0.000005). They further showed that microbiota richness correlated positively with Th17 for cases but not controls, whereas Bacteroidetes inversely correlated with Th17 for cases but not controls.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Many of the studies shown in Table 1 have been recently reviewed by Newland et al (19). The studies conducted so far suggest the presence of a disrupted or altered microbiota in MS patients when compared to healthy controls (12)(13)(14)(15)(16)(17)(18). All studies were performed in patients diagnosed with relapsing remitting MS, and in some the effects of immunomodulatory therapies were evaluated (13,18).…”
mentioning
confidence: 99%